Comparison of the percentage of umbilical cord nucleated red blood cells in preterm neonates during vaginal delivery and emergency cesarean section - Maryam Zakerihamidi; Elahe Heidari; Hassan Boskabadi (Wolters Kluwer Medknow Publications, 2024)
Background: There are insufficient and contradictory reports regarding the effect of delivery method on the rate of umbilical cord Nucleated Red Blood Cell (NRBC). Therefore, the present study aimed to compare the percentages of umbilical cord NRBC in vaginal delivery and emergency cesarean section (C-section) in preterm neonates. Materials and Methods: The present cross-sectional study was performed on mothers with vaginal delivery and C-section, from 2020 to 2021. The samples (n = 221) were preterm neonates selected using the convenience sampling method. The percentages of NRBC in neonates born by natural childbirth and by emergency C-section were measured and compared in this research. A researcher-made checklist, which included maternal and neonatal characteristics and laboratory evaluation, was used as a data collection tool. Results: The statistical population of thisresearch included 93 (42.10%) and 128 (57.90%) neonates born by vaginal delivery and by C-section, respectively.The mean (SD) score of gestational ages at birth was 30.75 (2.81) weeks. The mean (SD) score of umbilical cord NRBC level were estimated at 8.01 (5.93) and 25.64 (22.61) for the neonates born by natural childbirth and by emergency C-section, respectively (t=-8.43, df = 150, p<0.001). Statistically significant differences were observed in the gestational age (t=-3.36, df = 218, p = 0.001), fifth-minute Apgar score (t=-2.32, df = 200, p = 0.021), umbilical cord NRBC (t=-8.43, df = 160, p<0.001), and short-term prognosis (p = 0.032) between the two groups. It was also revealed that the number of NRBCs in the dead neonates was about 1.5 times higher than that in the discharged neonates. Conclusions: Based on the results of the present study, emergency C-section increased the mean of umbilical cord NRBC by three times, compared to that of normal delivery. Since an increase in the NRBC raises the risk of infant death, it is advisable to take steps to maintain the health of children by identifying high-risk neonates through umbilical cord NRBC measurement immediately after delivery and special care.